A Policy Framework for Mitigating the Impact of the COVID-19 Crisis - Moorty, Lalita; Mahajan, Sandeep; Andronova Vincelette, Gallina; Izvorski, Ivailo (World Bank, Washington, DC, 2020)
COVID-19 is a seismic shock the likes of which have not been seen in living memory. What makes it different? For one, it is a rolling combination of a global health pandemic and an economic crisis that is unfolding at an unprecedented pace. The impact is already devastating at both the human and economic levels, in mutually reinforcing ways. Second, the crisis has turned truly global in record time, to an extent that the 2008 global financial crisis (GFC) became only after half a year or later. The epicenter of the health crisis has shifted from China to Europe and now to the US. But the health and economic consequences are affecting every part of the inhabited world, with rising ferocity. Third, this is both a demand- and supply-side economic shock. The world has seen severe demand shocks (the Great Depression and the GFC) and severe supply shocks (the two World Wars, the Oil Crisis of the 1970s), but rarely the two at same time. The damage from the current crisis in Europe and Central Asia (ECA) and elsewhere is deep and multifaceted, wherein the adverse outcomes can be put in three main categories: human suffering, economic recession, and financial and corporate sector distress. The COVID-19, a major health crisis, has also quickly turned into an economic crisis, and threatens to become a serious financial crisis, with each acting in mutually reinforcing ways. The immediate policy response must focus on containing the virus outbreak and managing it in its three dimensions (health, economic, and financial and corporate).